INFLUENCE OF WORK MOTIVATION AND WORK ENVIRONMENT ON COMPETITIVE ADVANTAGE: STUDY OF INDONESIA AND CHINA TOURISM WORKERS - Indrayanto, Adi; Nugroho, Sigit W.D.; Nurfitri, Titi; Hongbo, Duan (Universitas Brawijaya, Indonesia, 2018)
This research is a study of the relationship between work motivation and work environment on the competitive advantage that is developed by creativity and innovation. The objective of this research is to analyze the influence of work motivation and work environment on creativity and innovation in creating competitive advantage. This research conducted at tourism location in Indonesia and China. The sample determined by purposive sampling. The total respondent from this research is 368 respondents consist of 181 from Indonesian and 187 from China. Employing Partial Least Square (PLS) analysis, the results from outer models, inner models, and hypotheses testing by t-test are as follows: Work motivation has positive significant influence toward creativity. Work environment has a significant influence on creativity. Creativity has positive significant influence toward innovative. The implication from the conclusion below, suggest that tourism workers should increase work motivation because it could give positive feedback to an organization. Increasing work motivation also can increase creativity on an individual in facing dynamic environment to create competitive advantage and win over competitors.